Prevalence of CYP2C8*2 and *3 among Eritreans and its Potential Impact on Artesunate/Amodiaquine Treatment - Habtemikael L; Russom M; Bahta I; Mihreteab S; Berhane A; Mårtensson A; Gil JP (Dove Medical Press, 2020)
Lidia Habtemikael,1 Mulugeta Russom,2 Iyassu Bahta,2 Selam Mihreteab,3 Araia Berhane,4 Andreas Mårtensson,1 Jose Pedro Gil1,5,6 1Department of Women’s and Children’s Health, International Maternal and Child Health (IMCH), Uppsala University, Uppsala, Sweden; 2National Medicines and Food Administration, Ministry of Health, Asmara, Eritrea; 3National Malaria Control Programme, Ministry of Health, Asmara, Eritrea; 4Communicable Diseases Control Division, Ministry of Health, Asmara, Eritrea; 5Department of Microbiology and Tumour Cell Biology, Karolinska Institute, Stockholm, Sweden; 6Biosystems & Integrative Sciences Institute, Faculty of Sciences, University of Lisbon, Lisbon, PortugalCorrespondence: Mulugeta RussomEritrean Pharmacovigilance Centre, National Medicines and Food Administration, Asmara, EritreaTel +291-7197450Fax +291-1-122899Email satiswt@gmail.comBackground: In Eritrea, artesunate–amodiaquine is the first-line treatment against uncomplicated malaria. Amodiaquine, which is mainly bio-transformed by CYP2C8, is known to be associated with adverse events of different severity. Extrapyramidal events are among the less common but have been reported with non-negligible frequency in Eritrea. This study was conducted to investigate the allele frequencies of CYP2C8*2 and *3, both associated with decreased amodiaquine metabolism, among the Eritrean population.Methods: During September–November 2018, dried blood samples from 380 participants and 17 patients who previously had experienced extrapyramidal symptoms following treatment of artesunate–amodiaquine were collected and PCR-RFLP genotyped for CYP2C8*2 and *3.Results: The allele frequencies of CYP2C8*2 and *3 were determined as 5.9% (95% CI: 4.4– 7.8) and 4.6% (95% CI: 3.2– 6.3), respectively. Four out of the 17 patients with extrapyramidal reactions showed to be carriers of the alleles.Conclusion: CYP2C8*2 and *3 frequencies among Eritreans were found to be intermediate between the documented for Caucasian and African populations. These findings, along with the alleles not being decisive for the occurrence of extrapyramidal events, might be of importance regarding the amodiaquine-containing malaria treatment in Eritrea. Furthermore, it suggests a significant proportion of slow amodiaquine metabolizers in the Sahel region, information of potential interest in the context of amodiaquine-involving seasonal malaria chemoprevention.Keywords: malaria, uncomplicated, artesunate/amodiaquine, CYP2C8, slow metabolizers